In vitro Sequestration of Molecular and Mass Spectra Characterized Metallophilic Cadmium Tolerant Bacteria for Sustainable Agriculture - Uqab, Baba; Nazir, Ruqeya; Ganai, Bashir Ahmad; Rahi, Praveen (Frontiers in Microbiology, 2022)
Due to industrialization, the contamination of toxic metals in soils is currently one of the major concerns to scientists worldwide. The presence of high concentrations of heavy metals including cadmium in the environment is mainly attributed to human activities. Being a highly toxic metal, cadmium can enter plant cell transporters usually used for the uptake of essential cations, such as iron, calcium, and zinc. This study deals with the appraisement of response and tolerance shown by various bacteria in varied cadmium concentrations (100–1,000 ppm). The optical density (OD) of the isolates was measured to determine the minimum inhibitory concentration (MIC) of cadmium. Isolated bacteria have been identified using 16S rRNA gene sequence and Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Among the 72 isolates, 07 (Bacillus pumilus, Enterobacter kobei, Klebsiella pneumonia, Pseudomonas mandelii, Pseudomonas putida, Pseudomonas avellanae, and Staphylococcus equorum), isolates had efficacy for cadmium tolerance and showed sequestration potential at varying MIC. Furthermore, K. pneumonia was observed to have the highest (900 ppm) tolerance for cadmium and the lowest (600 ppm) was shown by E. kobei. Besides, K. pneumonia showed the highest (75.2%) sequestration potential while the least (52.4%) potential was observed for P. putida. These cadmium tolerant species can be implemented in contaminated environments for detoxification and elimination of cadmium from these agricultural fields. Graphical Abstract